A cross-sectional analysis of dietary selenium intake and type 2 diabetes risk in adults: insights from NHANES 2011–2016 - Ge, Shenghui; Yu, Baowen; Yin, Xiao; Kong, Deyue; Luo, Yi; Ma, Jianhua; Xia, Wenqing (Frontiers in Nutrition, 2025)
ObjectiveWhile selenium exhibits antioxidant properties, its association with type 2 diabetes mellitus (T2DM) remains controversial. This study aimed to investigate the relationship between dietary selenium intake and T2DM risk in a nationally representative population.MethodsWe conducted a cross-sectional analysis of 2,170 adults from the National Health and Nutrition Examination Survey (NHANES) 2011–2016. Using weighted multivariable logistic regression, we estimated adjusted ORs with 95% CIs across selenium intake quartiles. Restricted cubic splines with three knots (10th, 50th, and 90th percentiles) were employed to characterize non-linear associations. Additionally, stratified analyses were performed based on age, sex, ethnicity, BMI, smoking status, and drinking status.ResultsA significant U-shaped relationship was observed between dietary selenium intake and T2DM risk (p for non-linearity = 0.042), indicating increased risk at both low and high intake extremes. In obese individuals (BMI ≥ 30 kg/m2), higher selenium intake was inversely associated with the risk of T2DM (ptrend = 0.016), suggesting a potential protective role in populations with elevated oxidative stress. No significant associations were found for supplemental or total selenium intake.ConclusionBoth insufficient and excessive dietary selenium intake may elevate the risk of T2DM, with an optimal range identified through non-linear modeling. Targeted selenium recommendations for obese individuals could mitigate diabetes risk, though longitudinal studies are needed to confirm causality. These findings highlight the importance of personalized nutrition strategies in high-risk populations.